Mississippian-Asselian (early carboniferous-early permian) foraminiferal faunas and biostratigraphy of the Shahreza-Abadeh regions (The Sanandaj-Sirjan Zone), Iran / Shirin Fassihi - Shirin , Fassihi (2017)
The Mississippian‒Asselian (Early Carboniferous‒Early Permian) foraminiferal faunas and biostratigraphy were studied in three sections of the Shahreza‒Abadeh regions, in the Sanandaj-Sirjan Zone, in Iran. These sections with a thickness of about 528‒1180 m are mainly composed of the siliciclastics and fossiliferous carbonates carbonates, apparently deposited in a shallow-water environment. The studied successions consist of Carboniferous Shishtu and Sardar groups and the uppermost Carboniferous‒Lower Permian Anarak Group. The sequence in question contains 217 species belonging to 75 genera within the six foraminiferal zones; namely, (1) the Uralodiscus rotundus - Glomodiscus miloni zone of a Viséan age, (2) the Plectostaffella jakhensis - Eostaffella pseudostruvei zone of a Voznesenian (earliest Bashkirian) age, (3) the Tikhonovichiella tikhonovichi - Profusulinella (Depratina) prisca - Aljutovella spp. zone of a Melekessian‒Vereian (latest Bashkirian–earliest Moscovian) age, (4) the Beedeina samarica - Taitzehoella mutabilis zone of a late Kashirian age, (5) the Fusulinella (Fusulinella) pseudobocki zone of an early Podolskian age, and (6) the Praepseudofusulina kljasmica zone of a latest Gzhelian‒Asselian age. Among the identified foraminifers, 21 genera and 37 species are reported for the first time in the Sanandaj-Sirjan Zone. The foraminiferal zones and their characteristic index species allow to correlate the Mississippian–Asselian sequence in the Sanandaj-Sirjan Zone with the foraminiferal biozonation acknowledged for the Mississippian–Asselian in the the Russian Platform, Southern and Northern Urals, Istanbul Terrane, Eastern and Central Taurides (Turkey), and Western Europe. These new foraminiferal faunas, furthermore, share some common species with the concurrent faunas of the Alborz, East Iran, and Central Iran. In this study, the foraminiferal assemblages of the Voznesenian (earliest Bashkirian) age, the Melekessian‒Vereian (latest Bashkirian‒earliest Moscovian) age, and also the Biozone MFZ11B (late early Viséan) are reported for the first time in the Sanandaj-Sirjan Zone. The study also presents the occurrence of 19 species of foraminifers for the first time in Iran.